Interferon γ receptor 2 gene variants are associated with liver fibrosis in patients with chronic hepatitis C infection. Issue 8 (29th June 2010) - Nalpas, Bertrand; Lavialle-Meziani, Roubila; Plancoulaine, Sabine; Jouanguy, Emmanuelle; Nalpas, Antoine; Munteanu, Mona; Charlotte, Frederic; Ranque, Brigitte; Patin, Etienne; Heath, Simon; Fontaine, Hélène; Vallet-Pichard, Anaïs; et al.
Abstract : Background: Only a minority of patients with chronic hepatitis C virus (HCV) infection develops severe liver fibrosis, a process that may be controlled by human genetic factors. Objective: To investigate the role of 384 single nucleotide polymorphisms (SNPs) located in 36 candidate genes related to the fibrogenesis/fibrolysis process. Methods: Patients with chronic HCV infection were gathered from two French cohorts (prospectively and retrospectively). The overall sample consisted of 393 HCV-infected subjects without known risk factors for fibrosis progression, including 134 patients with severe liver fibrosis and 259 without severe fibrosis. Results: Only two SNPs in strong linkage disequilibrium (LD) in the interferon γ receptor 2 gene ( IFNGR2 ) were significantly associated with liver fibrosis in both the prospective and the retrospective samples. The strongest association (p=8×10 −5 ) was observed with the G/A SNP rs9976971 with an OR of severe fibrosis for AA versus AG or GG subjects at 2.95 (95% CI 1.70 to 5.11). This effect was higher (p=9×10 −7 ) when taking into account the time of follow-up, and the hazard ratio of progression towards severe fibrosis for AA patients was 2.62 (1.76 to 3.91). Refined sequencing and analysis of the IFNGR2 region identified two additional variants in strong LD with rs9976971. No haplotypes derived from this cluster of four variants provided stronger evidence for association than rs9976971 alone. Conclusions: This identification of a cluster of four IFNGR2 variants strongly associated with fibrosis progression in chronic HCV infection underlines the role of IFNγ in the development of liver fibrosis that may pave the way for new treatments.